ADDRESSING THE LEARNING INVESTMENT PARADOX IN ASEAN DIGITAL LOGISTICS: DEVELOPMENT OF AN INTEGRATED ROTI-DBOM FRAMEWORK - Siti Norida Wahab; Hariadi Ismail; Hariyanto (LAND JOURNAL, 2026)
Employee learning investment in the ASEAN digital logistics sector has increased substantially, yet this growth has not consistently produced proportional improvements in cross-border logistics performance. This study examines this learning investment paradox by comparing evidence from PT Pos Logistik Indonesia and Pos Malaysia Berhad. PT Pos Logistik Indonesia recorded IDR 3.912 billion in education and training expenditure across 172 programs in 2023, while key cross-border performance indicators such as on-time delivery, complaint rate, customer satisfaction, and cost efficiency remained relatively stagnant. Pos Malaysia Berhad, despite implementing structured capability development through the Certified Wira programme and HRD Corp levy scheme, continues to face operational capability gaps in digital and cross-border logistics execution. This study develops an Integrated ROTI-DBOM Framework that combines Return on Training Investment, the Design-Build-Operate-Maintain cycle, and the Balanced Scorecard perspectives of financial, customer, internal business process, and learning and growth. The framework is further grounded in UNESCO’s four pillars of learning and Senge’s five disciplines of a learning organization. Using a conceptual study approach with comparative secondary data analysis, this paper proposes a reorientation of training management accounting from a cost-center paradigm to a strategically integrated value-center model. The study contributes to logistics management accounting by offering a lifecycle-based framework for linking training expenditure to measurable cross-border performance outcomes through a Learning Investment Portfolio.